Instagram and #Wellness: Uncovering Gender and Body Patterns - Ana Marta M. Flores; Rita Sepúlveda (Media and Communication)
The concept of “wellness” and its associated representations have become key aspects of modern culture, with social media platforms like Instagram playing a significant role. Not only do these platforms serve as spaces for the public expression of wellness-related topics, but they also influence public perceptions. This becomes particularly meaningful when these expressions are linked to gender. Our research explores how wellness and gender are depicted in popular Instagram posts. By analysing 300 public Instagram posts tagged with #wellness from 2023, we investigate whether traditional notions of gender and bodies are challenged or reinforced. Wellness is a multifaceted process, but our findings show that users often adhere to a narrow concept. To understand these representations, we focused on posts tagged with #wellness, particularly those in the physical category. The study employed a digital methods approach (Rogers, 2013) and thematic analysis (Braun & Clarke, 2006, 2021), uncovering three primary themes: Practices & Workout, Body & Expressions, and Clothing & Adornment. Predominantly, all themes in the context of wellness depict gender in a binary form and bodies as thin or athletic. These traditional gender and body norms are perpetuated on Instagram, reinforcing societal standards of beauty and body image. Instagram’s engagement logic preferentially promotes content conforming to dominant societal norms, strengthening these patterns. Alternative or counter-narratives, while they exist, often face challenges in gaining visibility due to both algorithmic biases and cultural predispositions. Although Instagram has the potential to offer a platform for such counter-narratives, our findings indicate that normative content continues to dominate in terms of visibility and engagement.